STUDI EFEKTIFITAS PERMA NOMOR 2 TAHUN 2008 TENTANG KOMPILASI HUKUM EKONOMI SYARIAH (KHES) SEBAGAI PEDOMAN DALAM PENYELESAIAN PERKARA EKONOMI SYARIAH DI PENGADILAN AGAMA - Darwin Darwin (Tamwil, 2015)
This study was focused on the Rules of Supreme Courts (PERMA) Number 2/2008 about the Compilation of Islamic Economy Laws (KHES). The sudy was classified into qualitative approach. The finding revealed that PERMA Number 2/2008 about KHES was run effectively in religious court since September 10th, 2008. Keywords: PERMA Number 2/2008, KHES, Religious Justice Court, Syariah Economy